PENGARUH MODEL PEMBELAJARAN SAINS TEKNOLOGI MASYARAKAT TERHADAP KETERAMPILAN BERPIKIR KRITIS - Fauziyansyah, Yudi Agus; Maryani, Enok; Nigrum, Epon (Indonesia University of Education, 2013)
This research was based on the importance critical thinking skills for learner. One of models which can develop critical thinking skills are learning model STS. For that, the researcher tried to apply the learning models STS with characteristic emphasis on process skills in problem-solving so can training the critical thinking skills. So that, the research aimed to determine the effect of the learning model STS critical thinking skills. The research method in this research are experimental method and use non equivalent pre test post test design. The subject in this research is consist of experimental group who using learning model STS and control group is using discussion method Instrumental research are using test, observation and assignment sheet. Statistical used in this research and use normality test, homogeneity test and hypothesis test using SPSS programme. The results showed that 1) There is no difference in students 'prior knowledge' before learning implemented 2) There are difference between the results of students post-test experimental group with the control group 3) There are difference between in students critical thinking skills between the experimental group with the control group. So that there is any effect for the influence of learning model STS for critical thinking skills Keywords : learning model STS, discussions method, the experimental design, critical thinking skills.